2015
DOI: 10.1007/s12016-015-8500-0
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Nailfold Videocapillaroscopy Pattern as Predictors of Digital Ulcers in Systemic Sclerosis: a Cohort Study and Review of the Literature

Abstract: Raynaud's phenomenon and digital ulcers (DUs) are frequent among systemic sclerosis (SSc) patients. Our aim was to investigate the diagnostic and predictive value for DU of endothelial dysfunction biomarkers (flow-mediated dilatation (FMD), serum levels of endothelin-1 (ET-1), and ADMA), angiogenic/angiostatic biomarkers (vascular endothelial growth factor (VEGF), endoglin, and endostatin), and nailfold videocapillaroscopy (NVC). We compared our results with a literature review. In a cohort study of 77 SSc pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 64 publications
4
42
1
Order By: Relevance
“…While the current study found that the capillary density on the third digit of the dominant hand was sufficient for predicting the risk of new DUs, it is still necessary to evaluate at least 4 digits per hand for the diagnosis of SSc in patients with Raynaud's phenomenon. The study also indicated that the NVC pattern may play a role in predicting DUs, confirming the results of smaller studies that have shown that the late SSc NVC pattern is associated with an increased risk of DUs . Ideally, future studies would encompass NVC‐based indices assessing eventual disease‐modifying characteristics of treatment on the clinical complications of SSc such as DUs .…”
Section: Discussionsupporting
confidence: 78%
“…While the current study found that the capillary density on the third digit of the dominant hand was sufficient for predicting the risk of new DUs, it is still necessary to evaluate at least 4 digits per hand for the diagnosis of SSc in patients with Raynaud's phenomenon. The study also indicated that the NVC pattern may play a role in predicting DUs, confirming the results of smaller studies that have shown that the late SSc NVC pattern is associated with an increased risk of DUs . Ideally, future studies would encompass NVC‐based indices assessing eventual disease‐modifying characteristics of treatment on the clinical complications of SSc such as DUs .…”
Section: Discussionsupporting
confidence: 78%
“…diffuse subtype of SSc, late pattern of capillaroscopy, history of DU or markers for endothelial dysfunction [912]. Various imaging methods have been suggested to measure vasculopathy in patients with systemic sclerosis and to link its extent to the existence of current or future digital ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies focused on capillaroscopic patterns (i.e. early, active and late) and found associations to the presence as well as the development of digital ulcers [11, 12, 2024]. While these studies have not provided concrete values of specificity and sensitivity, we calculated levels of around 36% and 89% respectively using their provided data [11, 12, 20, 23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have consistently shown that devascularization and distortion of the capillary architecture-which characterize late microvascular injury among patients with SSc-are strong predictors of complications involving target organs, such as the skin, lungs, heart, gastrointestinal tract, and kidneys (B) [28,[89][90][91], (C) [92], (D) [93].…”
Section: Should Nailfold Capillaroscopy Be Repeated During the Followmentioning
confidence: 99%